Politeness of the Minang Community in the Tourism Object Area in Dealing with Japanese Tourists with Aizuchi Culture - Adrianis; Asri, Dhiant (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Andalas, 2021)
The study focuses on politeness of merchants and managers in the Minang tourism area in the use of aizuchi towards Japanese tourists in Padang city. Politeness in terms of the language used by Minang merchants in tourism areas can be seen in the daily lives of those who use the Kato Nan Ampek culture. The ampek kato are kato malereng, kato mandaki, kato manurun, and kato mandata. Based on the five characteristics proposed by Mynard, there are only three characteristics, namely expressing confirmation, showing concern, and surprise. These characteristics indicate a cultural attitude that uses Kato Nan Ampek, namely kato mandaki and kato mandata. Politeness that is done to Japanese people who have aizuchi culture, namely the response to the interlocutor varies depending on the place. In general, merchants and tourism object managers are very polite in order to attract tourists to their business. Because of the limitations in mastering the Japanese language, the characteristic forms shown by the merchants are only in the form of confirmation by using the words はい (hai), はい、そうです (hai sou desu), and the form of one's attention in the form of そうですね (sou desune), expressing doubts by using the phrase わかりません (wakarimasen). Meanwhile, the politeness given by merchants and tourism managers is based on the functions put forward by Horiguchi, namely stating that the interlocutor is listening, understanding the conversation, agreeing, and expressing feelings.